Ocular Prosthesis Fabrication with Visible Light-Cured Resin Custom Tray: A Case Report - Upasana Panda; Mirna Garhnayak; Abhilash Mohapatra; Bodhisatta Mukherjee; Saroj Nehra; Gaurav Pal Singh (Institute of Medico-legal Publications Pvt Ltd, 2021)
A well fitting custom ocular prosthesis warrants an accurate impression of the anopthalmic socket. Problemarises when neither the stock ocular tray nor conformer is available or ill fitting in nature. This case reportelaborates the fabrication of an ocular prosthesis with emphasis on chair side method of custom ocular trayfabrication. Visible light cured resin denture base material has been used for preparation of ocular tray. Thismethod is simple, quick and precise.